Integracja systemów informacji przestrzennej z systemami wspomagania zarządzania - Laska, Maciej; Małachowski, Andrzej (Integration of Geographic Information Systems and Management Information Systems, 2005)
Traditional management information systems and decision support systems omit spatial relations between data and deliver managers the incomplete information, thus they can contribute to wrong conclusions and incorrect decisions. Organizations have to incorporate geoinformation technologies to manage and efficiently utilize their geographic information resources. The most predominant geotechnology is Geographic Information System (GIS) - a relatively new field that is introduced into the IS/IT/MIS environment. In this paper we will discuss how the basic concepts of GIS can be applied to and integrated with the enterprise information infrastructure. We will also show which functions and processes in the organization may be improved by the integration of GIS and the core of MIS.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 367-378